ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI PROVINSI JAWA TENGAH PERIODE 2010-2014 - Hapsari, Adinda Putri; Iskandar, Deden Dinar (EP FEB UNS, 2018)
This study aims to analyze the influence of capital expenditure, private investment, population, education on economic growth in the province of Central Java 2010-2014 years. The method of analysis used is panel data regression with fixed effect approach. The result of regression analysis shows that variable of capital expenditure, population, and education have a significant positive effect to economic growth. Private investment variable has negative and insignificant effect on economic growth, while health variable has significant negative effect to economic growth.